Surgical management of maxillary sinusitis of endodontic origin after reestablishing maxillary sinus floor healing through a nonsurgical approach: a case report - Eun-Sook Kang; Min-Kyeong Kim; Mi-Kyung Yu; Kyung-San Min (Restorative Dentistry & Endodontics)
When root canal infections breach the maxillary sinus floor (MSF), maxillary sinusitis of endodontic origin (MSEO) can result. This case illustrates the surgical management of MSEO following the nonsurgical reestablishment of the MSF. A 55-year-old woman presented with left facial pain and was diagnosed with MSEO originating from the left upper first molar. Despite undergoing nonsurgical root canal treatment, there was no evidence of bony healing after 6 months. However, cone-beam computed tomographic (CBCT) scans revealed the reestablishment of MSF. Subsequently, surgical intervention was carried out using a dental operating microscope. Two years after surgery, CBCT images indicated that the mucosal edema had resolved, and the MSF was well reestablished. Preserving the MSF is crucial for the success of endodontic surgery. When MSEO is present, the integrity of the MSF must be assessed to determine appropriate treatment options.